Caveolin 1 Modulates Aldosterone‐Mediated Pathways of Glucose and Lipid Homeostasis - Rene Baudrand; Nidhi Gupta; Amanda E. Garza; Anand Vaidya; Jane A. Leopold; Paul N. Hopkins; Xavier Jeunemaitre; Claudio Ferri; Jose R. Romero; Jonathan Williams; Joseph Loscalzo; Gail K. Adler; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundOveractivation of the aldosterone and mineralocorticoid receptor (MR) pathway is associated with hyperglycemia and dyslipidemia. Caveolin 1 (cav‐1) is involved in glucose/lipid homeostasis and may modulate MR signaling. We investigated the interplay between cav‐1 and aldosterone signaling in modulating insulin resistance and dyslipidemia in cav‐1–null mice and humans with a prevalent variant in the CAV1 gene. Methods and ResultsIn mouse studies, cav‐1 knockout mice exhibited higher levels of homeostatic model assessment of insulin resistance, cholesterol, and resistin and lower ratios of high‐ to low‐density lipoprotein (all P<0.001 versus wild type). Moreover, cav‐1 knockout mice displayed hypertriglyceridemia and higher mRNA levels for resistin, retinol binding protein 4, NADPH oxidase 4, and aldose reductase in liver and/or fat tissues. MR blockade with eplerenone significantly decreased glycemia (P<0.01), total cholesterol (P<0.05), resistin (P<0.05), and described enzymes, with no effect on insulin or triglycerides. In the human study, we analyzed the CAV1 gene polymorphism rs926198 in 556 white participants; 58% were minor allele carriers and displayed higher odds of insulin resistance (odds ratio 2.26 [95% CI 1.40–3.64]) and low high‐density lipoprotein (odds ratio 1.54 [95% CI 1.01–3.37]). Aldosterone levels correlated with higher homeostatic model assessment of insulin resistance and resistin and lower high‐density lipoprotein only in minor allele carriers. CAV1 gene expression quantitative trait loci data revealed lower cav‐1 expression in adipose tissues by the rs926198 minor allele. ConclusionsOur findings in mice and humans suggested that decreased cav‐1 expression may activate the effect of aldosterone/MR signaling on several pathways of glycemia, dyslipidemia, and resistin. In contrast, hyperinsulinemia and hypertriglyceridemia are likely mediated by MR‐independent mechanisms. Future human studies will elucidate the clinical relevance of MR blockade in patients with genotype‐mediated cav‐1 deficiency.